Designing Small Molecule Organic Solar Cells with High Open‐Circuit Voltage. Issue 3 (30th January 2017) - Kudrjasova, Julija; Van Landeghem, Melissa; Vangerven, Tim; Kesters, Jurgen; Heintges, Gaël H. L.; Cardinaletti, Ilaria; Lenaerts, Ruben; Penxten, Huguette; Adriaensens, Peter; Lutsen, Laurence; Vanderzande, Dirk; Manca, Jean; et al.
Abstract: Three extended 2, 5‐dithienylthiazolo[5, 4‐ d ]thiazole‐based small molecule chromophores are prepared via a sustainable direct arylation approach and their physicochemical and opto‐electrical material characteristics are analyzed toward integration in solution‐processed bulk heterojunction organic photovoltaics. Efficient charge separation and high values of the charge transfer state energy are derived from sensitive ground and excited state absorption and photoluminescence measurements on blends of the thiazolo[5, 4‐ d ]thiazole‐based electron donor components with the PC71 BM fullerene acceptor. Upon implementation in organic solar cells, a maximum power conversion efficiency of 2.7% and particularly high open‐circuit voltages (0.93−0.98 V) are observed, which are correlated to the charge transfer state energies as derived from photoluminescence, Fourier transform photocurrent spectroscopy and combined electrochemical and photophysical data. Furthermore, several loss processes at the origin of the modest short‐circuit current densities and fill factors are elucidated. Abstract : Push‐pull thiazolo[5, 4‐ d ]thiazole‐based small molecules are prepared via direct arylation and used as electron donors in bulk heterojunction organic solar cells. Dedicated spectroscopic analysis reveals efficient charge separation in blends with fullerenes and high values for the charge transfer state energies.